COMPARISON OF EXPERIMENTAL AND CALCULATION VALUES OF THE ELECTRIC FIELD GRADIENT TENSOR PARAMETERS FOR IMPURITY ATOMS 57 Fe3+ and 57m Fe 2+ B CuO (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
Absorption Mossbauer spectra of CuO samples: 57Fe at 295K they are a superposition of two quadrupole doublets, the parameters of which are practically independent of the iron concentration.Discrepancy between calculated and experimental values of quadrupole splitting of CuO samples: 57 Fe may be a consequence of aliv a - ribbon replacement of the Cu 2+  ion  with the Fe 3+  ion.